Legal Review on the Disparity of Judges' Decisions in Criminal Cases - Siti Nurazizah; Vina Humaira (Eastasouth Institute, 2022)
Every country thatDemocracy certainly has one of the most important characteristics, namely the independence of the judiciary and is responsible. The existence of judicial power in Indonesia has been justified. Law of the Republic of Indonesia Number 48 of 2009 states that judicial power according to the 1945 Constitution of the Republic of Indonesia is an independent power exercised by a Supreme Court and judicial bodies under it in the general court environment, the religious court environment, the military court environment, the state administrative court environment, and by a Constitutional Court, to administer justice to uphold law and justice. Mukti Arto in his book entitled “Ideal Conception of the Supreme Court” states that the existence of an independent judiciary is very important for three reasons: (a) the Court is the guardian of the Constitution; (b) Free trials are an element of a democracy; (c) Courts are the source of the rule of law.